In-situ resonance Raman measurements of a hybrid electrochromic cell with a gel redox I3-/I- electrolyte - Surca, Angelja Kjara (Acta chimica slovenica, 2003)
A hybrid electrochromic (HEC) device was constructed from optically active nanocrystalline WO3 film and transparent platinised SnO2Č F-glass electrodes encapsulating a gel redox electrolyte. The electrolyte was prepared from an organic-inorganic ICS-PPG precursor that was synthesized from bis end-capped triethoxy silane and poly(propyleneglycol)- bis-(2-amino- propyl) ether (MW = 4000). KI and I-2 in a molar ratio KIČ I-2 = 10Č 1 were a source of an I-3(-)žI- redox pair while valeric acid was used as a catalyst for the solvolysis reactions of the ICS-PPG precursor. The stability and kinetics of colouringžbleaching changes of the HEC device were determined by using in-situUV-visible spectroelectrochemical measurements between + 2 and - 2 V (CV, CC).
Keywords: elektrokemija; elektroliti; Ramanska spektroskopija; sončne celice